Impact of biofilms in simulated drinking water and urban heat supply systems. (13th August 2009) - Lopes, F.A.; Morin, P.; Oliveira, R.; Melo, L.F.
Biofouling and biocorrosion were studied in drinking water and heating water systems by forming biofilms on steel and on polymethylmetacrylate. In the drinking water system, biofilm development was more significant on corroded surfaces, suggesting that in these conditions they were largely protected from disinfection, probably because of sheltering and chlorine demand by corrosion products. In the urban heat supply system, results suggest a higher biofilm activity at lower pH. Sulphate-reducing bacteria were detected in the urban heating biofilms, but little corrosion was observed on steel coupons. Results indicate that surface and bulk medium properties, as well as bacterial diversity are determinant parameters when studying biofouling and biocorrosion.